Are Antarctic ozone variations a manifestation of dynamics or chemistry? - Tung, K.-K.; Ko, M. K. W.; Rodriguez, J. M.; Sze, N. D. (1986)
The existence of a reverse circulation cell with rising motion in the polar lower stratosphere is suggested as an explanation for the temporal behavior of the ozone column density in the Antarctic region. The upwelling brings ozone-poor air from below 100 mbar to the stratosphere, possibly contributing to the observed ozone decline in early spring. At the same time, the Antarctic stratosphere might contain a very low concentration of NO(x), a condition that could favor a greatly enhanced catalytic removal of O3 by halogen species. It is argued that heterogeneous processes and formation of OClO by the reaction BrO+ClO - OClO+Br before and after the polar night might help to suppress the NO(x) levels during the early spring period.